Tuning the band gap and carrier concentration of titania films grown by spatial atomic layer deposition: a precursor comparison. Issue 20 (9th September 2021) - Armstrong, Claire; Delumeau, Louis-Vincent; Muñoz-Rojas, David; Kursumovic, Ahmed; MacManus-Driscoll, Judith; Musselman, Kevin P.
Abstract : Titanium isopropoxide and tetrachloride precursors are compared with SALD. The effects of Cl contamination on TiO2 's growth (agglomeration) and band gap (decrease) are reported before demonstrating the TiO2 's performance in a photovoltaic device. Abstract : Spatial atomic layer deposition retains the advantages of conventional atomic layer deposition: conformal, pinhole-free films and excellent control over thickness. Additionally, it allows higher deposition rates and is well-adapted to depositing metal oxide nanofilms for photovoltaic cells and other devices. This study compares the morphological, electrical and optical properties of titania thin films deposited by spatial atomic layer deposition from titanium isopropoxide (TTIP) and titanium tetrachloride (TiCl4 ) over the temperature range 100–300 °C, using the oxidant H2 O. Amorphous films were deposited at temperatures as low as 100 °C from both precursors: the approach is suitable for applying films to temperature-sensitive devices. An amorphous-to-crystalline transition temperature was observed for both precursors resulting in surface roughening, and agglomerates for TiCl4 . Both precursors formed conformal anatase films at 300 °C, with growth rates of 0.233 and 0.153 nm s −1 for TiCl4 and TTIP. A drawback of TiCl4 use is the HCl by-product, which was blamed for agglomeration in the films. Cl contamination was the likely cause of band gap narrowing and higher defect densities compared to TTIP-grown films. The carrier concentration of the nanofilms was found to increase with deposition temperature. The films were tested in hybrid bilayer solar cells to demonstrate their appropriateness for photovoltaic devices.